2021
DOI: 10.1038/s41597-021-00956-1
|View full text |Cite
|
Sign up to set email alerts
|

Electric vehicle charging stations in the workplace with high-resolution data from casual and habitual users

Abstract: Problems of poor network interoperability in electric vehicle (EV) infrastructure, where data about real-time usage or consumption is not easily shared across service providers, has plagued the widespread analysis of energy used for transportation. In this article, we present a high-resolution dataset of real-time EV charging transactions resolved to the nearest second over a one-year period at a multi-site corporate campus. This includes 105 charging stations across 25 different facilities operated by a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…As far as workplace charging is concerned, this practice represents a valid charging opportunity, especially when it is perceived as cheaper than charging at home or when home charging is not available. Usage data show regular patterns on working days, with a low rate of exploitation on holidays [126,127].…”
Section: Analysis Of Infrastructure Usagementioning
confidence: 99%
“…As far as workplace charging is concerned, this practice represents a valid charging opportunity, especially when it is perceived as cheaper than charging at home or when home charging is not available. Usage data show regular patterns on working days, with a low rate of exploitation on holidays [126,127].…”
Section: Analysis Of Infrastructure Usagementioning
confidence: 99%
“…Recent advances in real-time data collection allow us to leverage highly granular digital data from mobile platforms to estimate effects about travel decisions [13][14][15][16][17] . First, digital data provide users with instant information about travel options and costs using geolocation and Global Positioning System (GPS) tracking 7 .…”
Section: High-resolution Mobility Data and The No Ride Zonementioning
confidence: 99%
“…Jiang et al [44] suggested that swappable batteries might be used to improve the consumer's intention, considering the drastic decline in overall charging time that would result. Asensio et al [45] explored the effect of charging at the workplace; the number of charging stations and the location of charging stations was very significant. Adhikari et al [42] and Amin et al [43] found that consumer demands for charging stations in the public domain, such as supermarkets, parks, and restaurants, are trivial, and they are keener to charge EVs at home.…”
Section: Availability Of Charging Facilitymentioning
confidence: 99%